Identification of Serotype in Culture Negative Pneumococcal Meningitis Using Sequential Multiplex PCR: Implication for Surveillance and Vaccine Design - Saha, Samir K. (Public Library of Science, 2008)
BACKGROUND: PCR-based serotyping of Streptococcus pneumoniae has been proposed as a simpler approach than conventional methods, but has not been applied to strains in Asia where serotypes are diverse and different from other part of the world. Furthermore, PCR has not been used to determine serotype distribution in culture-negative meningitis cases. METHODOLOGY: Thirty six serotype-specific primers, 7 newly designed and 29 previously published, were arranged in 7 multiplex PCR sets, each in new hierarchies designed for overall serotype distribution in Bangladesh, and specifically for meningitis and non-meningitis isolates. Culture-negative CSF specimens were then tested directly for serotype-specific sequences using the meningitis-specific set of primers. PCR-based serotyping of 367 strains of 56 known serotypes showed 100% concordance with quellung reaction test. The first 7 multiplex reactions revealed the serotype of 40% of all, and 31% and 48% non-meningitis and meningitis isolates, respectively. By redesigning the multiplex scheme specifically for non-meningitis or meningitis, the quellung reaction of 43% and 48% of respective isolates could be identified. Direct examination of 127 culture-negative CSF specimens, using the meningitis-specific set of primers, yielded serotype for 51 additional cases. CONCLUSIONS: This PCR approach, could improve ascertainment of pneumococcal serotype distributions, especially for meningitis in settings with high prior use of antibiotics.